2019
DOI: 10.2147/ndt.s200501
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive function, depression, and anxiety in patients undergoing radical prostatectomy with and without adjuvant treatment</p>

Abstract: Background Prostate cancer (PC) is one of the most common malignant tumors in developed countries. Both PC and treatment for PC have an adverse impact on physical and mental well-being, and are associated with decreased quality of life. The aim of the present study was to examine the relationship between neuropsychological symptoms and clinical course in PC patients undergoing radical prostatectomy with or without adjunct therapy. Methods The cohort comprised 100 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Urinary incontinence is widely recognised as one of the most debilitating complications following prostatectomy, with significant impact of cancer survivors’ quality of life. Recent research on the psychological burden of PPI has demonstrated the extent of its detrimental effects, including increased cognitive dysfunction, anxiety and depression [ 19 , 20 ]. As a consequence, the selection of surgical treatment for PPI, and predicting the outcomes of surgery are critical metrics for prostate cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence is widely recognised as one of the most debilitating complications following prostatectomy, with significant impact of cancer survivors’ quality of life. Recent research on the psychological burden of PPI has demonstrated the extent of its detrimental effects, including increased cognitive dysfunction, anxiety and depression [ 19 , 20 ]. As a consequence, the selection of surgical treatment for PPI, and predicting the outcomes of surgery are critical metrics for prostate cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and severity of depression and anxiety symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS). Cognitive function was assessed using the computer-based test battery (Neurotest), which comprises the following [22]: -Simple reaction time test (SRT): to evaluate the speed and correctness of simple reactions to stimuli. The patient's task is to respond to the stimulus in the form of a green circle appearing on the computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…We have found two cases with memory disorders and prostatic hypertrophy (5%). Jarzemski et al [64], reported delayed memory dysfunction in patients undergoing both surgical and adjunct therapy for radical prostatectomy.…”
Section: Memory Disorders and Prostatic Diseasesmentioning
confidence: 99%